Teaching Attentive Reading and Motivated Writing through Digital Editing. - GAILEY, AMANDA (CEA Critic, 2014)
The article discusses the use of digital editing in teaching attentive reading and motivated writing. It explains the pedagogical value of digital tool Text Encoding Initiative (TEI) in digital textual representation. The evolution of digital humanities pedagogy is noted. Also discussed are the pedagogical benefits of digital editing which include discovery and empowerment, writing with a purpose and for an audience, and transferable skills.